Effect of Linker Substituent on Layers Arrangement, Stability, and Sorption of Zn-Isophthalate/Acylhydrazone Frameworks - Rortocki, Kornel; Jedrzejowski, Damian; Hodorowicz, Maciej; Senkovska, Irena; Kaskel, Stefan; Matoga, Dariusz (Crystal Growth and Design, 2018)
A series of mixed-linker metal-organic frameworks [Zn2(Xiso)2(pcih)2]n containing substituted isophthalate linkers (Xiso2- X = OH or CH3 or NH2 or H) and 4-pyridinecarbaldehyde isonicotinoyl hydrazone pillars (pcih) have been prepared by using both solution and mechanochemical methods. Single-crystal X-ray diffraction reveals their interdigitated two-dimensional structures with different arrangements of layers, dependent on hydrogen bonding and CH···π interactions involving the substituents and/or linkers. These supramolecular interactions are responsible for the formation of interlayer pores of various volumes, shapes, and dimensionality. All materials exhibit selective gas adsorption of CO2 over N2 with diverse profiles. Polar groups (OH and NH2) of the isophthalate linkers increase chemical affinity to carbon dioxide as well as hydrolytic and thermal stability of the frameworks.
CRIS-Team Scopus Importer:2022-04-14